2020
DOI: 10.1155/2020/8975078
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Lung Nodules Based on Deep Residual Networks and Migration Learning

Abstract: The classification process of lung nodule detection in a traditional computer-aided detection (CAD) system is complex, and the classification result is heavily dependent on the performance of each step in lung nodule detection, causing low classification accuracy and high false positive rate. In order to alleviate these issues, a lung nodule classification method based on a deep residual network is proposed. Abandoning traditional image processing methods and taking the 50-layer ResNet network structure as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Adopting effective classification techniques can reduce FP detection and, thus, significantly improve the accuracy of nodule identification and reduce the difficulty of subsequent tasks. For example, Wu et al [ 78 ] developed a deep residual network to classify lung nodules. For this, the authors adopted a transfer-learning-based 50-layer Res-Net structure with global average pooling.…”
Section: Classificationmentioning
confidence: 99%
“…Adopting effective classification techniques can reduce FP detection and, thus, significantly improve the accuracy of nodule identification and reduce the difficulty of subsequent tasks. For example, Wu et al [ 78 ] developed a deep residual network to classify lung nodules. For this, the authors adopted a transfer-learning-based 50-layer Res-Net structure with global average pooling.…”
Section: Classificationmentioning
confidence: 99%
“…Yang et al [24] had used CT scan images and initially identified the pulmonary parenchyma area by lung segmentation and used DenseNet for classification that gave an accuracy of 92% with an AUC of 0.98 on the test set. Wu et al [25] have used lung regions extracted as nodules and no nodules using radiologist's annotations and then used four different methods to classify between the two classes using 10-fold cross-validation. Authors tested on Curvelet and SVM, VGG19, Inception V3, and ResNet 50 and further obtained the best accuracy of 98.23% with AUC of 0.99.…”
Section: Background Literaturementioning
confidence: 99%
“…Deep Learning (DL) [15][16][17][18][19][20] is a branch of AI that was mostly used for COVID classification. There are many research studies using Transfer Learning (TL)-based [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Along with the TB classification, CNN based approaches found in the literature are also utilized for lung nodule classification from the entire input image [30], [31]. In [30] lung nodules are classified using an automated classification technique. The authors utilized the pre-trained CNN architecture i.e.…”
Section: A Classification Based On Entire Input Imagementioning
confidence: 99%